Commentary of Skandasvāmin & Maheśvara on the Nirukta - Skandasvāmin (Panini Vaidika granthamala, 1982)
Commentaries on Yāska's Nirukta, classical commentary on Nighnṭu, anonymous thesaurus of Vedic synonyms, setting forth Vedic etymology.